Constituents and antimicrobial properties of blue honeysuckle: a novel source for phenolic antioxidants - Palíková, Irena; Heinrich, Jan; Bednár, Petr; Marhol, Petr; Kren, Vladimír; Cvak, Ladislav; Valentová, Katerina; Růzicka, Filip; Holá, Veronika; Kolár, Milan; Simánek, Vilím; Ulrichová, Jitka (Journal of agricultural and food chemistry, 2008)
The fruit of Lonicera caerulea L. (blue honeysuckle; Caprifoliaceae) and its phenolic fraction were analyzed for nutrients and micronutrients. The phenolic fraction was prepared from berries percolated with 0.1% H3PO4 and SPE using Sepabeads SP207. The sugar and lipid content was analyzed by HPLC and GC-MS. The total content of anthocyanins was determined using the pH differential absorbance method and aliphatic acids by capillary electrophoresis. MicroLC-MS/MS was used for determination of cyanidin-3-glucoside (the predominant anthocyanin), 3,5-diglucoside, and 3-rutinoside, paeonidin-3-glucoside, 3,5-diglucoside, and 3-rutinoside, delphinidin-3-glucoside and 3-rutinoside, pelargonidin-3-glucoside, 3,5-diglucoside, and 3-rutinoside, quercetin, its 3-glucoside, and 3-rutinoside, epicatechin, protocatechuic, gentisic, ellagic, ferulic, caffeic, chlorogenic, and coumaric acids. The phenolic fraction displayed Folin-Ciocalteu reagent reducing (335 +/- 15 microg of gallic acid equivalent/mg) and DPPH and superoxide scavenging activity (IC50 12.1 +/- 0.1 and 115.5 +/- 6.4 microg/mL) and inhibited rat liver microsome peroxidation (IC50 160 +/- 20 microg/mL). The freeze-dried fruit and its phenolic fraction reduced the biofilm formation and adhesion to the artificial surface of Candida parapsilosis, Staphylococcus epidermidis, Escherichia coli, Enterococcus faecalis, and Streptococcus mutans.
Keywords: Microsomes, Liver; Lonicera; Fungi; antioxidancia; rostlinné extrakty; anthokyaniny; Bacterial Adhesion; Bacteria; houby; fenoly; Anti-Infective Agents; Plant Extracts; Antioxidants; Biofilms; peroxidace lipidů; biofilmy; Lipid Peroxidation; Anthocyanins; Phenols; bakteriální adheze; antiinfekční látky; jaterní mikrozomy